Exploring Visually Impaired Students' Experiences with NVDA in Learning English: A Case Study in Inclusive Education - Lintang Kusumaningtyas; Pryla Rochmahwati (FOSTER: Journal of English Language Teaching, 2026)
This study aimed to examine the experiences of visually impaired students in utilizing Non-Visual Desktop Access (NVDA) as a medium for English language learning in an inclusive classroom at SMA Muhammadiyah 1 Ponorogo, Indonesia. This research used a qualitative method with a case study approach. Three visually impaired students were sampled for the study. Data collection was conducted through an interview and observation method. The data was analyzed qualitatively with the help of thematic analysis. The research was also guided by the Technology Acceptance Model and the Constructivist Learning Theory. The study found that NVDA is an effective medium for English language learning for visually impaired students. It helps the students access English language texts easily. NVDA also helps the students to be independent and build confidence in completing English language learning tasks. However, the research also found that NVDA has some limitations. It cannot handle non-text and multimodal content such as images, tables, graphs, and visually dense presentation materials. The research concluded that NVDA is not only an assistive technology but also a pedagogical support for English language learners.